FORM OPTIMIZATION OF A SURFACE COMBATANT BY MEANS OF COMPUTATIONAL FLUID DYNAMICS - Sener, Bekir; Yilmaz, Tamer (YILDIZ TECHNICAL UNIV, 2012)
The traditional ship design process is often under the control of geometric modeling of the boat form. After this, model performance is analyzed with various simulations. If the result is not satisfactory, the iterative steps are repeated until the desired performance is obtained. These hull forms, which revealed by these method, are usually a negotiated solution rather than the optimum, that partially reflects the different performance criteria. In this work an automatic ship hull form optimization methodology is developed based Simulation Driven Design method with using new generation of design, analysis and optimization software combination. For this purpose, parametric modeling software called FRIENDSHIP-Framework is used to collect the optimization process under one roof and handle the process automatically. Aforementioned methodology is used to develop a systematical hull form series for frigate-type surface warships. Next stage, two hull form are chosen as sample and a multi-objective optimization process is performed. After optimization, initial and optimum hull forms are compared to show that how to improve the resistance and seakeeping results with some local changes.
Keywords: Computational fluid dynamics; parametric modeling; multi-objective optimization; Engineering